Real-Time Imaging of HIF-1α Stabilization and Degradation - Moroz, Ekaterina; Carlin, Sean; Dyomina, Katerina; Burke, Sean; Thaler, Howard T.; Blasberg, Ronald; Serganova, Inna (PLOS ONE, 2009)
HIF-1α is overexpressed in many human cancers compared to normal tissues due to the interaction of a multiplicity of factors and pathways that reflect specific genetic alterations and extracellular stimuli. We developed two HIF-1α chimeric reporter systems, HIF-1α/FLuc and HIF-1α(ΔODDD)/FLuc, to investigate the tightly controlled level of HIF-1α protein in normal (NIH3T3 and HEK293) and glioma (U87) cells. These reporter systems provided an opportunity to investigate the degradation of HIF-1α in different cell lines, both in culture and in xenografts. Using immunofluorescence microscopy, we observed different patterns of subcellular localization of HIF-1α/FLuc fusion protein between normal cells and cancer cells; similar differences were observed for HIF-1α in non-transduced, wild-type cells. A dynamic cytoplasmic-nuclear exchange of the fusion protein and HIF-1α was observed in NIH3T3 and HEK293 cells under different conditions (normoxia, CoCl2 treatment and hypoxia). In contrast, U87 cells showed a more persistent nuclear localization pattern that was less affected by different growing conditions. Employing a kinetic model for protein degradation, we were able to distinguish two components of HIF-1α/FLuc protein degradation and quantify the half-life of HIF-1α fusion proteins. The rapid clearance component (t1/2 ∼4–6 min) was abolished by the hypoxia-mimetic CoCl2, MG132 treatment and deletion of ODD domain, and reflects the oxygen/VHL-dependent degradation pathway. The slow clearance component (t1/2 ∼200 min) is consistent with other unidentified non-oxygen/VHL-dependent degradation pathways. Overall, the continuous bioluminescence readout of HIF-1α/FLuc stabilization in vitro and in vivo will facilitate the development and validation of therapeutics that affect the stability and accumulation of HIF-1α.